Understanding the New School Meal Standards - Jenna Norris; Karla P. Shelnutt; Gail P. Kauwell (EDIS)
If you have school-age children, you may have heard that the 2012 school year brought major changes to the meals children eat at school. All meals provided through the School Breakfast and National School Lunch Programs now must be consistent with the USDA’s Dietary Guidelines for Americans. This 6-page fact sheet was written by Jenna Norris, Karla P. Shelnutt, and Gail P. A. Kauwell, and published by the UF Department of Family Youth and Community Sciences, October 2013.